Serine Biosynthesis and Regulation in Haemophilus influenzae - Pizer, Lewis I. (1969)
Nutritional mutants of Haemophilus influenzae requiring l-serine for growth were shown to be deficient in their capacity to synthesize serine-phosphate from 3-phosphoglycerate. On the basis of the correlation between this block and the requirement for an exogenous supply of the amino acid, it was concluded that the “phosphorylated” pathway is the only pathway used by H. influenzae for serine biosynthesis. Serine inhibits serine-phosphate production, thereby regulating its own synthesis in a manner analagous to the Enterobacteriaceae. A mutant strain that required either serine or tryptophan for growth was normal in serine-phosphate synthesis and regulation. It was concluded that this strain probably has a tryptophan synthetase with an increased Michaelis constant for serine.